Malignant Phyllodes Tumor by the Example of a Clinical Case - G. P. Korzhenkova; A. A. Kasymova (Вестник рентгенологии и радиологии, 2021)
Breast cancer is the most common cancer in women worldwide, but there are also rarer types of breast neoplasms in clinical practice. One of these neoplasms is a phyllodes tumor. Due to the rare occurrence of phyllodes tumors and few studies of this pathology, there is today no information about the precise etiology and pathogenesis of this tumor. For the same reasons, it is very difficult to correctly and timely diagnose breast cancer, which requires both a highly qualified radiologist who first detects this disease in a patient and a pathologist who establishes a final morphological diagnosis. Existing studies, such as mammography and ultrasound, do not have reliable criteria for the diagnosis of phyllodes tumors and are unable to differentiate different histological types of these neoplasms, which further complicates the diagnosis of this pathology. Also, standards for the treatment of patients with this diagnosis have not been fully approved. The paper describes a clinical case of successful surgical treatment for a malignant phyllodes tumor of the left breast in a 47-year-old patient.